Cholestyramine in the management of recurrent diarrhoea in infancy - Pitono Soeparto; Subiyanto M. S.; Haroen Soerasid (Paediatrica Indonesiana, 1982)
Ninety nine infants and children aged between 3 months to 3 years with recurrent diarrhoea, were devided into 2 groups. Each of which receiving resp. Cholestyramine (53 patients) and the usual modess of diarrhoeal therapy (46 patients).Comparative study of the response to treatment was however possible in only 38 patients of the cholestyramine group and 35 patients of rite non choleslyrlllnine group. There was no difference in the response to the treatment between cholestyramine and non cholestyramine groups.